Theory of computation - Tourlakis, George J. (Hoboken, N.J. : Wiley, 2012)
"In the (meta)theory of computing, the fundamental questions of the limitations of computing are addressed. These limitations, which are intrinsic rather than technology dependent, may immediatly rule out the existence of algorithmic solutions for some problems while for others they rule out efficient solutions. The author's approach is anchored on the concrete (and assumed) practical knowledge about general computer programming, attained readers in a first year programming course, as well as the knowledge of discrete mathematics at the same level. The book develops the metatheory of general computing and builds on the reader's prior computing experience. Metatheory via the programming formalism known as Shepherdson-Sturgis Unbounded Register Machines (URM)--a straightforward abstraction of modern highlevel programming languages--is developed. Restrictions of the URM programming language are also discussed. The author has chosen to focus on the highlevel language approach of URMs as opposed to the Turing Machine since URMs relate more directly to programming learned in prior experiences. The author presents the topics of automata and languages only after readers become familiar, to some extent, with the (general) computability theory including the special computability theory of more "practical" functions, the primitive recursive functions. Automata are presented as a very restricted programming formalism, and their limitations (in expressivity) and their associated languages are studied. In addition, this book contains tools that, in principle, can search a set of algorithms to see whether a problem is solvable, or more specifically, if it can be solved by an algorithm whose computations are efficient. Chapter coverage includes: Mathematical Background; Algorithms, Computable Functions, and Computations; A Subset of the URM Language: FA and NFA; and Adding a Stack to an NFA: Pushdown Automata"--
"The book develops the metatheory of general computing and builds on the reader's prior computing experience. Metatheory via the programming formalism known as Shepherdson-Sturgis Unbounded Register Machines (URM)--a straightforward abstraction of modern high-level programming languages--is developed. Restrictions of the URM programming language are also discussed. The author has chosen to focus on the high-level language approach of URMs as opposed to the Turing Machine since URMs relate more directly to programming learned in prior experiences"--
1 Mathematical foundations -- 2. Algorithms, computable functions and computations -- 3. A subset of the URM language; FA and NFA -- 4. Adding a stack to a NFA: pushdown automata -- Computational complexity.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Computable functions; Functional programming languages; Computable functions; Functional programming languages; MATHEMATICS -- Discrete Mathematics; Computable functions; Functional programming languages; Computable functions; Functional programming languages; Electronic books; Electronic books